PERAN JOB CRAFTING DALAM MENINGKATKAN KREATIVITAS KARYAWAN : A SCOPING REVIEW - Rosalina, Sekar Ayu; Muhid, Abdul (J-MIND (Jurnal Manajemen Indonesia), 2025)
Employee creativity is an important aspect in driving innovation and organizational competitiveness. One strategy that has been proven effective in enhancing creativity is job crafting, which is the proactive behavior of employees in adjusting their work to better suit their preferences, strengths, and personal goals. This study aims to map the literature related to the relationship between job crafting and creativity through a scoping review approach. A total of 21 scientific articles published between 2020 and 2025 were analyzed using the PRISMA protocol and analyzed thematically and bibliometrically using VOSviewer. The results of the study show that job crafting generally has a positive relationship with creativity, both directly and through the mediation of psychological variables such as work engagement, self-efficacy, and psychological capital. Contextual factors such as leadership, organizational climate, and individual-organization fit also moderate these relationships. These findings have important implications for organizational policy development and managerial interventions to create a work environment that supports employee initiative and creativity.